2013
DOI: 10.5897/ajb10.1027
|View full text |Cite
|
Sign up to set email alerts
|

Removal of nitrogen from anaerobically digested swine wastewater using an anoxic/oxic (A/O) process complemented with a sulfur-packed biofilter

Abstract: A modified lab-scale anoxic/oxic process was designed incorporating an upflow sulfur-packed biofilter for the treatment of anaerobically digested swine wastewater. In this study, chemical oxygen demand (COD), NH 4 +-N and NO x-N removal efficiencies were investigated. The experimental results showed that by increasing the internal recycle ratio from 1 to 3, the overall performance of the system improved. Organics removal efficiency was found to be fairly high and stable and the average total chemical oxygen de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
0
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
(41 reference statements)
6
0
0
Order By: Relevance
“…The average removal efficiency of COD was 77.2%. This result obtained is quite similar to the study conducted by [10] and similar with the result obtained by [11] . In this study, the average removal of COD was 64.3, 65.2, 68.0, 85.1 and 90.3% with influent and effluent concentration of 95.2, 99.4, 147.1, 108.9; 70.1mg/l and 34, 14.7, 47.0, 16.2 and 6.9mg/l respectively (see table 2 and fig.…”
Section: Organic Materials Removal (Cod)supporting
confidence: 92%
“…The average removal efficiency of COD was 77.2%. This result obtained is quite similar to the study conducted by [10] and similar with the result obtained by [11] . In this study, the average removal of COD was 64.3, 65.2, 68.0, 85.1 and 90.3% with influent and effluent concentration of 95.2, 99.4, 147.1, 108.9; 70.1mg/l and 34, 14.7, 47.0, 16.2 and 6.9mg/l respectively (see table 2 and fig.…”
Section: Organic Materials Removal (Cod)supporting
confidence: 92%
“…The overall removal efficiency of COD was 77.2%. This result obtained is quite similar to the study conducted by Gurung et al (2011) who observed an average COD removal rate of 85% when the organic loading rate was 0.19 kg COD/m 3 /d and it is also similar with the result obtained by Rim and Han (2000) who observed an average TCOD removal rate of 80 to 95% when the organic loading rate was maintained in the range of 0.4 to 3.1 kg COD/m 3 /d. In this study, the average removal of COD was 64.3, 65.2, 68.0, 85.1 and 90.3% with effluent concentration of 34, 14.7, 47.0, 16.2 and 6.9mg/L with HRT of 1.5, 2, 4, 5 and 3 h respectively (Table 3).…”
Section: Analytical Proceduressupporting
confidence: 91%
“…The average concentrations of NH 4 + -N in the influent, anoxic oxic and constructed wetland during the experimental operations were 22, 23.8, 8.3 and 5.7 mg/L, respectively (Table 4). The average removal efficiency of total NH 4 + -N was 74.1% almost similar to that obtained by Gurung et al (2011). The average removal of NH 4 + -N was 60.3, 63.0, 64.4, 71 and 91.8 % with effluent concentration of 6.2, 6.7, 6.2, 6.1 and 3.1 mg/L operated with HRT of 2, 3, 5, 1.5 and 4 h, respectively (Table 4 and Fig.…”
Section: Nhsupporting
confidence: 84%
“…The overall removal efficiency of COD was 70.4%. This result obtained is quite similar to the study conducted by [8,9] . In this study, the average removal of COD was 42, 68, 74, 83, and 85% with effluent concentration of 34, 17.5, 11.7, 7.7 and 15.9mg/l under HRT of 1.5, 4, 2, 3 and 5hrs, with recycle ratios of 3, 2 and 1 respectively.…”
Section: Organic Materials Removal (Cod)supporting
confidence: 82%
“…+ -N and NO 3 --N removal The overall removal of NH 4 + -N by the reactor was 85% quite similar to that obtained by [8] . The average concentrations of NH 4 + -N in the influent, anoxic oxic and artificial wetland during the experimental operations were 11, 2.4, 1.1 and 1.5mg/L respectively.…”
Section: Nhsupporting
confidence: 60%